Panasonic P2 workflow with Final Cut Pro and the HVX200 - Kadner, Noah (Peachpit Press, 2012)
"Learn all about the Panasonic HVX200 with Final Cut Pro 7! Condensing years of Noah Kadner's expertise and know-how into easy-to-follow demonstrations and workflows, the video is broken into four sections: P2 pre-production, production : shooting for post, HD post-production with Final Cut Pro, and advanced workflows. Noah has answered thousands of HVX200 and FCP-related questions during his years spent as a forum leader in HVX200 message boards like 2-pop.com, CreativeCow.net and DVXuser.com. He's also spent years as an Apple Certified Pro instructor in Final Cut Studio and as a systems integrator and private consultant for 24p HD production and editing in Hollywood. Now he brings you all of that knowledge and experience in this master class. Attention Windows users-although this course utilizes Final Cut Pro for its examples, you'll find the topics highly useful for most other editing platforms as well including Avid and Adobe Premiere. Discover the P2 workflow secrets of your DVCPRO HD camera and learn how to get the maximum in post-production from Final Cut Pro 7. The course features over two hours of original content broken down into learning modules with interactive demonstrations and easy to understand, real-world examples. This video also applies to other Panasonic P2-based HD and SD cameras like the HPX170, HPX500, HPX502, SPX800, HPX2000 and HPX3000. P2 field workflow, 720p and 1080i variable frame rates, open format timeline editing, P2 ingest, metadata management techniques, editing system shopping lists, P2 store and P2 drive data archive strategies, transferring P2 to hard drive, 1394 host mode output to Apple Color output for 24p course, P2 content management software, P2 Log Pro HD, Log Native MXF, editing with Raylight, and more ..."--Resource description page.